Population genetic processes in introduction of fish - Salmenkova, E A (Genetika, 2008)
Introductions of alien species (populations) acquired a global scale, becoming a major factor of environmental change. Population-genetic and ecological studies of these species promote understanding of evolutionary change and mechanisms of adaptation of the species introduced into a novel environment. This knowledge is of interest also with regard to conservation biology in connection with restoring endangered or extinct populations. The transplanted populations are subject to the founder effect and gene drift, which entails loss of genetic variation, inbreeding depression, and reduction of fitness of the introduced species. However, the decrease in the quantitative variability (additive genetic variance, which is directly affected by selection) prove to be significantly less than the loss in neutral molecular genetic variation. Maintenance of genetic variation at the level providing establishment of the invasive species requires a high number of introduced individuals and multiple introductions from different populations of the species. Introductions are accompanied by hybridization and genetic introgression of the invader with the indigenous species, which augments the variability and viability of the former, but are extremely deleterious to the latter. Adaptive changes of morphological and ecological traits and the formation of the population-genetic structure in the new area occur very rapidly. The allied genetic divergence of the introduced population from the donor one may be directly or indirectly associated with the adaptation processes. Transplantation of anadromous salmonid species among hatcheries undertaken to increase the population numbers (i.e., introductions within the natural range) were of low efficiency owing to conservative local adaptations and low fitness of the transplanted fish. However, sometimes these transplantations were successful, if they involved geographically close populations with common origin and common evolutionary history. Numerous studies yield negative genetic, ecological, and ecosystemic effects of introduction of alien species and populations, which should be taken into account when planning transplantations.